Diltiazem aggravates testicular function impairment induced by cyclosporine A or tacrolimus in unilateral nephrectomised rats. (28th February 2019) - Lin, Yun; Zhang, Jinxiang; Lei, Wei; Li, Miaoyuan; Zhang, Zhi; Lu, Yanmeng; Chen, Linqiang; Yang, Jin; Liang, Jianjian; Chen, Yehui
Abstract: The aim of this study was to elucidate the reproductive toxicity of the coadministration of diltiazem and cyclosporine A or tacrolimus. Testicular development, semen quality, sex hormones and testicular tissues were assessed in unilateral nephrectomised (UN) rats, including the control group, UN group, UN+CsA group, UN+FK506 group, UN+Rapa group, UN+CsA+Dil group and UN+FK506+Dil group. The testicular coefficient, the sperm number and the sperm motility were lower in the treatment groups (except UN+FK506) than in the control and UN groups (all p < 0.05). The lowest sperm number and motility were identified in the UN+CsA+Dil group, followed by the UN+CsA group. The proportion of abnormal sperm was higher in the UN+CsA and UN+CsA+Dil groups than in the control and UN groups, respectively ( p < 0.05). The plasma concentrations of sex hormones were changed in the treatment groups. Dil can increase the blood concentrations of CsA and FK506 (◇ p < 0.05, ◆ p < 0.05). Therapeutic doses of these agents induced morphological changes in the testicular tissue and ultrastructural changes in the testosterone, mesenchymal cells and supporting cells. Our present study suggests that Dil can increase the testicular toxicity of CNIs (calcineurin inhibitors, including CsA and FK506) by enhancing the plasma concentrations of CNIs.